2010
DOI: 10.1016/j.addbeh.2010.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of social norms media marketing in reducing drinking and driving: A statewide campaign

Abstract: This research evaluated the efficacy of a high-intensity social norms media marketing campaign aimed at correcting normative misperceptions and reducing the prevalence of drinking and driving among 21-to-34-year-olds in Montana. A quasi-experimental design was used, such that regions of Montana were assigned to one of three experimental groups: social norms media marketing campaign, buffer, and control. Four random samples of Montanans between the ages of 21 and 34 were assessed at four time points over 18 mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
104
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 218 publications
(108 citation statements)
references
References 21 publications
2
104
0
2
Order By: Relevance
“…Additionally, the use of social media campaigns emphasizing safer sexual practices that are specifically created for Latino youth may be an effective tool for promoting perceived norms supporting such behaviors. The latter strategy has been effective at reducing heavy alcohol use among college students (Moreira, Smith, & Foxcroft, 2009;Perkins et al, 2010) and may be an effective mechanism for reaching Latino youth, especially those who engage in substance use, as they may be less willing to take part in intervention programs. Also consistent with prior research among other minority adolescents, reports of consistent condom use in this sample of Latino adolescents (overall, 53% reported using condoms consistently) were consistent with prior studies conducted among Latino/Hispanic youth and young adults .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the use of social media campaigns emphasizing safer sexual practices that are specifically created for Latino youth may be an effective tool for promoting perceived norms supporting such behaviors. The latter strategy has been effective at reducing heavy alcohol use among college students (Moreira, Smith, & Foxcroft, 2009;Perkins et al, 2010) and may be an effective mechanism for reaching Latino youth, especially those who engage in substance use, as they may be less willing to take part in intervention programs. Also consistent with prior research among other minority adolescents, reports of consistent condom use in this sample of Latino adolescents (overall, 53% reported using condoms consistently) were consistent with prior studies conducted among Latino/Hispanic youth and young adults .…”
Section: Discussionmentioning
confidence: 99%
“…These perceptions have changed despite the emergence of societal norms opposing tobacco use in public and media coverage about excessive alcohol use and driving. 96 …”
Section: Arguments For and Against Legalization Or Decriminalization mentioning
confidence: 99%
“…Perkins et al (2010) report results from a field experiment run in Montana, where surveys revealed that college students systematically overestimate the fraction of peers consuming alchoolic beverages. In the experiment, a random sample of college students were exposed to the (true) information that the overwhelming majority of the people in the state and of the students on campus consumes moderate quantities of alchol.…”
Section: Literature Reviewmentioning
confidence: 99%